Outcome of surgery for reconstruction of fractures of the acetabulum. The time dependent effect of delay. - Madhu, R; Kotnis, R; Al-Mousawi, A; Barlow, N; Deo, S; Worlock, P; Willett, K (2006)
This is a retrospective case review of 237 patients with displaced fractures of the acetabulum presenting over a ten-year period, with a minimum follow-up of two years, who were studied to test the hypothesis that the time to surgery was predictive of radiological and functional outcome and varied with the pattern of fracture. Patients were divided into two groups based on the fracture pattern: elementary or associated. The time to surgery was analysed as both a continuous and a categorical variable. The primary outcome measures were the quality of reduction and functional outcome. Logistic regression analysis was used to test our hypothesis, while controlling for potential confounding variables. For elementary fractures, an increase in the time to surgery of one day reduced the odds of an excellent/good functional result by 15% (p = 0.001) and of an anatomical reduction by 18% (p = 0.0001). For associated fractures, the odds of obtaining an excellent/good result were reduced by 19% (p = 0.0001) and an anatomical reduction by 18% (p = 0.0001) per day. When time was measured as a categorical variable, an anatomical reduction was more likely if surgery was performed within 15 days (elementary) and five days (associated). An excellent/good functional outcome was more likely when surgery was performed within 15 days (elementary) and ten days (associated). The time to surgery is a significant predictor of radiological and functional outcome for both elementary and associated displaced fractures of the acetabulum. The organisation of regional trauma services must be capable of satisfying these time-dependent requirements to achieve optimal patient outcomes.